Pemberdayaan Pembudidaya Ikan Melalui Pemberian Bantuan Bibit Ikan Bandeng di Desa Growong Kidul, Pati, Jawa Tengah - Setyono, Bagus Dwi Hari; Pebrianti, Ni Luh Mutiara; Maudina, Finda; Suprianto, Beni; Santoso, Budi; Affandi, Rangga Idris; Diamahesa, Wastu Ayu (Fakultas Teknik, Universitas PGRI Banyuwangi, 2023)
The empowerment program for milkfish farmers is an effort to enhance productivity and the well-being of the fishing community in Growong Kidul Village, Pati Regency, Central Java. The program's implementation includes the distribution of quality milkfish fingerlings to milkfish farmers as part of community engagement. The program aims to improve the technical knowledge of milkfish farming, strengthen the capacity of aquaculture infrastructure, and support the sustainability of the fisheries industry in the region. The methods employed include technical training, the provision of quality milkfish fingerlings, and assistance in the maintenance and marketing of milkfish farming products. Throughout the engagement activities, the community has shown great enthusiasm and participation. This is evident in the number of involved milkfish farmers, high attendance rates, active participation in discussions, and field activities. Ensuring the sustainability of this program is essential given the significant potential for milkfish farming development, especially in post-harvest processing.